Factors Affecting Career Development of Students in Class XI Accounting of SMK Negeri 3 City of Padang - Effendy Mave, Sofiyan (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the existence of students who do not know information about further education and the skills needed in one field of work and the existence of students who do not know the forms of careers that will develop and are needed in the future. The purpose of this study is to describe the factors that influence the career development of students in class XI Accounting at SMK Negeri 3 Padang seen from: 1) Genetic factors. 2) Factors of environmental conditions. 3) Learning factors. 4) The skill factor to face the task. This research was conducted using a quantitative descriptive method. The research population was 92 students who were selected by total sampling technique with 92 participants. The instrument used is a questionnaire. Meanwhile, for data analysis using percentage classification. Based on the results of research on the factors that influence the career development of students in class XI Accounting at SMK Negeri 3 Padang City, it can be concluded: that the factors that affect career development are seen from: 1) The genetic factors of students are in the fairly large category. 2) Factors of environmental conditions are in the category of many. 3) Learning factors are in quite a lot category. 4) The skill factor in facing the task is in the quite a lot category. From the results of this study, it can be recommended to BK teachers in order to provide direction for career choices to students according to their abilities, talents and interests.